SISTEM INFORMASI PENJUALAN BAJU ADAT NIAS PADA TOKO WARISTO BERBASIS WEB - Laia, Sadarman; Siringoringo, Rimbun; Lumbantoruan, Gortap (Universitas Methodist Indonesia, 2023)
Along with the times, information technology is experiencing increasingly rapid changes in various fields. As in trading business, information technology has provided many benefits in trading business. The problem with the Warristo Store is that there is no system that can assist employees in recording sales of goods, data collection, stock reports and sales reports. The solution to solving this problem is to design an information system that can make it easier for employees to do their work by using several programming applications. The results of the research conducted and the information system that has been designed are to help employees in the process of recording sales of goods, collecting goods data, transaction reports and sales reports easily and being able to convey information about the latest goods to consumers easily.